(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The English language is a vast and versatile linguistic landscape, characterized by its richness and adaptability. One of the intriguing features of English is the use of abbreviations and shortenings, which play a crucial role in both written and spoken communication. Abbreviations and shortenings are essential tools for condensing information, saving time, and enhancing clarity in various contexts. It is essential to delve into the world of abbreviations and shortenings in English, exploring their classification, usage, and significance.